Small satellites and CubeSats: Survey of structures, architectures, and protocols. (4th September 2018) - Davoli, Franco; Kourogiorgas, Charilaos; Marchese, Mario; Panagopoulos, Athanasios; Patrone, Fabio
Summary: The space environment is still challenging but is becoming more and more attractive for an increasing number of entities. In the second half of the 20th century, a huge amount of funds was required to build satellites and gain access to space. Nowadays, it is no longer so. The advancement of technologies allows producing very small hardware components able to survive the strict conditions of the outer space. Consequently, small satellites can be designed for a wide set of missions keeping low design times, production costs, and deployment costs. One widely used type of small satellite is the CubeSat, whose different aspects are surveyed in the following: mission goals, hardware subsystems and components, possible network topologies, channel models, and suitable communication protocols. We also show some future challenges related to the employment of CubeSat networks. Abstract : A brief general survey on small satellites and CubeSats is provided, touching mission goals, hardware subsystems and components, network topologies, channel models, and communication protocols. Future challenges and open issues are pointed out.